Foreign Language Anxiety in EFL Classroom Instructions - Rabby, G. (University of Jaffna, 2025)
Foreign Language Anxiety (FLA) significantly influences students’ self assurance, involvement, and overall language skills in English as a Foreign Language (EFL) setting. This research investigates the factors contributing to and consequences of FLA among secondary school students in Bangladesh, incorporating perspectives from student-teachers and language experts. A qualitative research design was employed, using surveys, semi-structured interviews, and Focus Group Discussions (FGDs) to gather in-depth insights into students’ experiences with language learning anxiety, specifically in speaking, listening, reading, and writing. The data were analyzed using thematic analysis. The findings reveal that FLA is driven by various elements such as fear of errors, discomfort in speaking English, exam pressure, and limited exposure to English beyond the classroom. Additionally, traditional teaching methods amplify anxiety across all language areas. Student-teachers identified challenges in addressing FLA while following strict curriculum guidelines, while language specialists stressed the importance of adopting interactive, student-focused teaching methods to alleviate anxiety. This study highlights the need for strategies in the classroom that create a more supportive and interactive learning environment. By encouraging peer collaboration, using communicative teaching methods, and fostering a positive atmosphere, anxiety levels can be reduced, thereby enhancing language learning. The study adds to the understanding of FLA in Bangladesh’s EFL context and offers practical recommendations for curriculum designers, educators, and policymakers to improve English language teaching.
Keywords: Foreign language anxiety; EFL classroom; Educational-reform; Communicative teaching; Teaching techniques